Measuring Financial Performance in the Absence of Objective Measures: an Evidence from Indonesia Local Restaurants - Josua Tarigan; Rafel Romero Hirawanto; Jean Dautrey; Saarce Elsye Hatane (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2019)
The purpose of this research is to explore the paths between the SERVQUAL dimensions, customer satisfactionand customer loyalty towards the financial performance in Indonesialocal restaurants. Researchers in Indonesia often encounter problems obtaining objective measures of financial performance in privately-held companies, especially restaurants industries. The authors help fill this knowledge gap by extended the study of service quality into financial performance. A quantitative approach was employed, using 26-items, five-point Likert-scale questionnaire administrated to 150 customers and 50 restaurant owners or managers. The data analysis technique that was used in this research was the Partial Least Square (PLS). The research showed that there is a strong consistent link between service quality, customer satisfactionand customer loyalty towards the financial performance.Additionally, customer loyalty have the role that strengthens the impact of customer satisfaction to the financial performance